Security Design And Testing of Lan and Wlan Network in Mikrotik Router Using Penetration Testing Method FROM Mitm Attack - Haeruddin . (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2020)
The growth of device user is always increasing and the costs are not expensive. Users already have several sophisticated end user networking tools for daily use, including laptops, smartphones and tablets. For internet access users use LAN and WLAN network services in several public areas such as restaurants, schools / campuses, hotels and offices. Activities done by the users are data and banking transactions. These activities relate to crucial data such as user data including usernames, passwords, accounts, emails and other sensitive data. Mikrotik Router is a router with an affordable price and complete features for both LAN and WLAN networks so that many administrators use this device. The most common attack used on the network is Man in the Middle Attack, which is actively tapping on the user's network connection, where traffic from the user before reaching the destination or when going through a Mikrotik router will be diverted through the attacker's network without the user's knowledge so that user communication can be read. Therefore a network security system on a Mikrotik router is needed to avoid such attacks. In testing the security system that has been made, it needs the right method, one of which is penetration testing. From the results of testing using the penetration testing method, results and solutions will be obtained to maintain network security.Keywords: Penetration Testing, Man in The Middle Attack, Wireless Security, Router dan Wireless Mikrotik.